The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2196/mental.4004
|View full text |Cite
|
Sign up to set email alerts
|

Patient Smartphone Ownership and Interest in Mobile Apps to Monitor Symptoms of Mental Health Conditions: A Survey in Four Geographically Distinct Psychiatric Clinics

Abstract: BackgroundDespite growing interest in mobile mental health and utilization of smartphone technology to monitor psychiatric symptoms, there remains a lack of knowledge both regarding patient ownership of smartphones and their interest in using such to monitor their mental health.ObjectiveTo provide data on psychiatric outpatients’ prevalence of smartphone ownership and interest in using their smartphones to run applications to monitor their mental health.MethodsWe surveyed 320 psychiatric outpatients from four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
130
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(149 citation statements)
references
References 10 publications
5
130
2
5
Order By: Relevance
“…Nowadays, more patients own smartphones and are interested to use them to monitor their health (Torous, Chan, et al, 2014;Torous, Friedman, & Keshavan, 2014). According to Ben-Zeev and colleagues (2013) advanced technologies can support self-management of mental illnesses, but to be feasible they need to be designed addressing real requirements and specific preferences of their final user.…”
mentioning
confidence: 99%
“…Nowadays, more patients own smartphones and are interested to use them to monitor their health (Torous, Chan, et al, 2014;Torous, Friedman, & Keshavan, 2014). According to Ben-Zeev and colleagues (2013) advanced technologies can support self-management of mental illnesses, but to be feasible they need to be designed addressing real requirements and specific preferences of their final user.…”
mentioning
confidence: 99%
“…Studies specifically examining interest in ICT for behavioral health education or intervention have reported variable results. Tourus and colleagues found that approximately half of patients (49%) recruited from four psychiatric clinics across the U.S. reported accessing general health information via smartphone in the previous 6 months, but 71% reported interest in using a smartphone to monitor mental health symptoms [36]. In contrast, Sharpe and colleagues found that only 29% of persons living with HIV who were recruited from five clinical sites in Florida reported interest in using a cell phone app to selfmanage drinking, though there were significant differences based on respondents' drinking levels, with those with hazardous drinking being more likely to express interest [37].…”
Section: Principal Results and Comparison With Prior Workmentioning
confidence: 99%
“…Uptake of apps has generally been slow in MH, as MH organizations were not eligible to receive federal start-up funding for IT infrastructure. Mobile apps offer 1) portability for access anytime, anywhere, regardless of patient geography and transportation barriers; 2) an inexpensive option versus traditional desktop computers; and 3) additional features (e.g., context-aware interventions and sensors [65] with real-time feedback. MH app demand is high across censusdesignated areas, generations, and, to a degree, age, with less use by older adults [65].…”
Section: Innovations or Additions To Regular Traditional Treatmentsmentioning
confidence: 99%
“…Mobile apps offer 1) portability for access anytime, anywhere, regardless of patient geography and transportation barriers; 2) an inexpensive option versus traditional desktop computers; and 3) additional features (e.g., context-aware interventions and sensors [65] with real-time feedback. MH app demand is high across censusdesignated areas, generations, and, to a degree, age, with less use by older adults [65]. Text messaging may be higher in urban areas [66] than rural areas [67].…”
Section: Innovations or Additions To Regular Traditional Treatmentsmentioning
confidence: 99%